The effect of education based on a health belief model in women's practice with regard to the Pap smear test. (June 2016) - Daryani, Sara; Shojaeezadeh, Davoud; Batebi, Azizollah; Charati, Jamshid Yazdani; Naghibi, Abolhassan
Abstract: Cervical cancer is the third most common cancer diagnosis and cause of death among gynecologic cancers. An appropriate strategy for the early detection of cancer is the Pap smear test used as an effective screening method. One of the models of behavior change used is the health belief model. The aim of this study was to determine the effect of education based on the health belief model in women's practice concerning the Pap smear test. This study was a controlled quasi-experimental study conducted on 120 women aged 20–65 years; the samples were randomly divided into two groups of 60 persons: an intervention group (under education) and a control group (without education). The women were then evaluated in two stages: before intervention and 2 months after intervention. The training was held in two 1.5-h sessions. Before education, 23.3% of women in the case group and 31.7% in the control group had undergone a Pap smear, but after education, 31.7% of those in the case group and 3.3% of those in control group underwent Pap smear. There was not a significant difference before education between the two groups ( P  = 0.414), but after education there was a significant difference between the two groups in terms of women's practice ( P  = 0.001). In the case group a significant difference before and after intervention in terms of constructs ( P  < 0.0001) was found, but in the control group, at the end of study, the difference from baseline was significant only in terms of perceived susceptibility ( P  = 0.042) and perceived severity ( P  = 0.002). Education based on the health belief model was effective in increasing women's practice concerning the Pap smear test. In this regard, eliminating defects in the field of health policy through increasing public education programs concerning the Pap smear test, and courses based on the barriers and benefits of the Pap smear test, can be effective in increasing performance and improving the behaviors of cervical cancer screening.